Experimental Study of Cable Force Measurement on Cable-Stayed Bridges Based on Vibration Method - Aisyah, Aisyah; Suhendro, Bambang; Aminullah, Akhmad (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2024)
This study investigates cable force estimation in cable-stayed bridges through a vibration-based approach, utilizing experimental data measured using an accelerometer sensor. In the initial phase of the research, the frequency data measured by accelerometers is validated through numerical modeling using the Midas Civil software. Additionally, besides employing the string formula, this study adopts formulas proposed by [1] to predict cable forces in two cable-stayed bridges in Indonesia. The estimated cable forces using both formulas are then compared with the actual cable forces measured during the lift-off test. The analysis results indicate that most of the cable frequency data is valid, with differences of less than 7% between the measured frequencies and numerical results. However, a significant difference is observed in one cable, BA-M11, with differences of up to 50.9%. This suggests that the mode order and frequency values measured for this cable are not valid. Through a numerical approach, accurate mode orders and frequencies are determined, enabling confident use of the measurement data for cable force estimation in the case of cable BA-M11. Furthermore, when the validated mode orders and frequency values are used with both the string formula and Yu’s proposed formulas, the results show that Yu’s formulas tend to provide more accurate estimations compared to the string theory, with average differences in cable force estimation of approximately 4.33% and 2.97% relative to the lift-off force. The contribution of this research lies in the utilization of numerical verification to correct inaccuracies in accelerometer-measured mode orders and frequency values. Subsequently, armed with validated mode orders and frequency values, Yu’s proposed formulas demonstrate superior accuracy in predicting cable forces compared to the string theory when both are compared with lift-off test data.